EVALUASI KEBIJAKAN PERATURAN DAERAH KOTA GORONTALO NOMOR 1 TAHUN 2018 TENTANG KETERTIBAN UMUM - Mokodompit, Athariq; Baderan, Umar Sako; Karim, Dian Fitriani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to evaluate the implementation of Regional Regulation (Perda) Number 1 of 2018 concerning Public Order in Gorontalo City using the CIPP evaluation model (Context, Input, Process, Product) developed by Daniel L. Stufflebeam. The regulation was established to ensure social order and control the increasing number of street beggars, buskers, and street children. However, despite its implementation, the phenomenon continues to rise annually. The research adopts a qualitative descriptive approach, using data collected through observation, in-depth interviews, and documentation involving key stakeholders, including the Social Affairs Office, the Civil Service Police Unit (Satpol PP), and street actors themselves. The results reveal that, based on the Context indicator, the policy was formulated as a response to a real social problem, yet its focus remains limited to law enforcement without addressing structural issues such as poverty, unemployment, and family dysfunction. From the Input perspective, institutional coordination between Satpol PP and the Social Affairs Office exists but lacks sufficient funding, personnel training, and continuous public outreach. The Process dimension indicates that the policy execution is reactive, short-term, and lacks systematic coordination or post-rehabilitation monitoring. The Product evaluation shows that while periodic enforcement actions have been conducted, they have not significantly reduced the number of street beggars and performers, which continues to fluctuate. Overall, the implementation of Perda No. 1 of 2018 has produced administrative compliance but has yet to achieve meaningful social transformation. To enhance policy effectiveness, a shift toward human-centered and empowerment-based approaches is essential, emphasizing cross-sector collaboration, sustainable rehabilitation programs, and inclusive social interventions